(untitled) (Physical Education, Health and Social Sciences, 2025)
Breast cancer is among the most common cancers worldwide, primarily affecting women but also occurring in men. While its exact cause remains unknown, several risk factors have been identified, including age, family history, genetic mutations (BRCA1, BRCA2), hormonal influences, lifestyle, and environmental exposures. Recent research has highlighted various genetic, epigenetic, and proteasomal markers that improve diagnosis and treatment. Key biomarkers include BRCA1/BRCA2, Ki67, p53, Cyclin D1 mutation, TP53 mutation, HER2 amplification, DNA methylation patterns, microRNAs (miRNAs), and androgen receptors (ARs). These markers play a crucial role in personalized medicine, enabling precise diagnosis and tailored therapies. For instance, HER2 amplification helps determine suitability for targeted treatments like trastuzumab. Similarly, miRNAs regulate gene expression, offering insights into tumor behavior and therapeutic response. Despite advancements, identifying the most effective biomarkers remains a challenge for researchers and clinicians. Optimizing these markers could enhance treatment strategies, reduce costs, and improve patient outcomes. Ongoing investigations into emerging biomarkers may lead to better interventions, ultimately supporting breast cancer management and care.